Performance of smallholder soybean farmers in Ghana; evidence from Upper West Region of Ghana - Francis Akabo Asodina; Faizal Adams; Fred Nimoh; Bright Owusu Asante; Amos Mensah (Journal of Agriculture and Food Research, 2021)
The economic importance of soybean towards poverty alleviation and food security is gaining wider popularity and common acceptance among smallholder farmers in sub-Sahara Africa, especially in Ghana. Commercial soybean cultivation is relatively new in Ghana; hence it has recently benefited from several productivities enhancing innovation/technologies. However, despite these efforts, productivity has remained low. This paper investigates factors affecting production efficiency among commercial soybean farmers, across the three commercial districts of the Upper West region of Ghana. A cross-sectional data collected from 271 soybean farmers were used to investigate technical efficiency of soybean production. The overall mean technical efficiency estimate is 59% with a scale elasticity of 0.89-indicating a huge scope for efficiency improvement. The result shows that, farmers experience in soybean production heavily influenced technical efficiency of output. With the existing technology and production resources, soybean farmers can improve their current levels of soybean production by 41% through the adoption of best production practices.